DEALING WITH THE ECONOMIC AND PSYCHOLOGICAL EXPERIENCE ECONOMY IN LOCAL COMMUNITIES - Tetyana NIKOLAYCHUK (Eastern European Journal of Regional Studies, 2022)
Protected areas and other natural territories are very important part of the Ukrainian economy. Due to the numerous possibilities of protected areas, it can occupy a significant part of the post-war reconstruction's destinations.The methodological approaches of protected areas development are considered as tools of economic and innovative regional development and expansion of investment flows. The post-war market of Ukraine depends on the the recovery level of the country's population, because the innovative forms of economic activity launching presupposes the existence of a healthy society ready of reforms and changes.Taking into account given the above, it is actualized the necessity to find out the essence and role of the facilities of nature reserve fund in the system of balanced economically efficient use of nature, their place in the financial and market infrastructures, the definition of the investment potential of reserve areas. The investigation of the market without inter-study differences was conducted by a quantitative literature review (a meta-analysis). Forming indicators of the most vulnerable society groups were analyzed by the systematization method. The main vectors of innovative growth in the EU countries and the adapting possibility of these tools to the Ukrainian economy were formed by the comparative method. As a result of research, the author analyzed economic, organizational, environmental and social principles protected areas increasing, it is established is considered the protected areas as a code of multitask development and economic stimulation to coperate with business entities.